Pelatihan Dan Pendampingan Manajemen Pemasaran dan Keuangan Untuk Mendukung Kemandirian Ekonomi Pondok Nurul Furqon Tomia Wakatobi Sulawesi Tenggara - Fais Faizul Hannan; Moh Syahrul Muzammil; Sinta Bella (LP3M IAIFA Kediri, 2025)
Nurul Furqon Islamic Boarding School located in Tomia, Wakatobi Regency, Southeast Sulawesi, has great potential in developing the economic independence of students through entrepreneurial activities. However, the main challenge faced is the lack of understanding and skills in marketing and financial management. This Community Service Activity aims to provide training and assistance in managing business finances and product marketing strategies, in order to increase the capacity of students in managing businesses independently and sustainably. The methods used are interactive training, field practice, and intensive assistance in preparing financial reports and utilizing digital media for marketing. The results of the activity show that students and boarding school managers are starting to be able to prepare simple financial reports such as cash books, profit and loss reports, and other transaction records. On the marketing side, they are starting to utilize social media, brochures, and other digital promotional media to expand market reach. This program has a positive impact in fostering an entrepreneurial spirit and increasing the economic independence of Nurul Furqon Islamic Boarding School.